Real-world survival outcomes in first-line ibrutinib-treated patients with high-risk CLL/SLL - John N. Allan; Tao Ran; Zhijie Ding; Jinghua He; Alex Bokun; Zaina P. Qureshi; Susan M. O’Brien (Blood Advances)
Abstract: In patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL), high-risk cytogenetic features such as del(17p), del(11q), and unmutated immunoglobulin variable heavy chain (IGHV) may be associated with unfavorable outcomes. In this large retrospective cohort study, data from a nationwide electronic health record–derived deidentified database were analyzed to assess real-world overall survival (rwOS) among patients treated with first-line (1L) ibrutinib with and without high-risk cytogenetic features (ie, del(17p), del(11q), unmutated IGHV). Inverse probability of treatment weighting was used to account for differences in patient characteristics between cohorts. Of 1242 patients included, 969 and 273 had high- and non–high-risk CLL/SLL, with a mean age of 70.0 and 70.8 years, and a median follow-up of 32 and 31 months, respectively. Within the high-risk cohort, 32.9%, 36.7%, and 58.7% had the presence of del(17p), del(11q), and unmutated IGHV, respectively. The median rwOS was not reached for either cohort; the hazard ratio (HR) comparing rwOS between the 2 cohorts was 1.09 (95% confidence interval [CI], 0.79-1.51). In a sensitivity analysis in which del(11q) was not part of the high-risk definition, similar results were found, with a HR of 1.19 (95% CI, 0.86-1.64) and median rwOS not reached for either cohort. Similarly, among the subgroup of patients with Medicare coverage, the HR was 0.98 (95% CI, 0.63-1.53), and median rwOS was not reached. In this real-world study using a large community health care data set, there was no difference in rwOS between patients treated with 1L ibrutinib with and without high-risk cytogenetic features.